Entada rheedii seeds thioamides, phenolics, and saponins and its antiulcerogenic and antimicrobial activities - Mona M. Okba, Sally A.W. El Awdan, Miriam F. Yousif & , Kadriya S. El Deeb, Fathy M. Soliman (Journal of Applied Pharmaceutical Science, 2018)
Entada rheedii (Fabaceae) seeds are used against diarrhea and stomach aches. This study aims at scientifically validate its ethnomedicinal uses. Seeds ethanol (70%) extract (EE) was prepared by percolation. Antibacterial and antiviral activities of EE and isolated compounds were determined using agar well diffusion and MTT assays, respectively. Anti-ulcerogenic activity was evaluated using ethanol-induced ulcer model. Four phenolics: protocatechuic acid C1, protocatechuic acid methyl ester C2, 1,3,4-trihydroxybenzene glucoside C3, phaseoloidin C4, three thioamides: entadamide A C5, entadamide A-β-d-glucopyranoside C6, entadamide C C7, and two saponins: rheedeioside A C8 and rheedeioside B C9 were isolated from EE. EE, C4, C5, and C8 evidenced significant (p Ë‚ 0.05) antiulcerogenic activity. Strong antibacterial activity was reported for EE, C1, and C7. C4 exhibited moderate (35% inhibition) antiviral activity. This study provides scientific validation of the seed ethnomedicinal use in treating gastric ailments and as antimicrobial.
Keywords: Entada rheedii, rheedeioside A, entadamide A, phaseoloidin, gastric ulcer, antibacterial.